Why Do the Externalist Criteria of Justification Essentialy Fail? - Nuhlíček, Martin (Organon F, 2013)
The article concerns two basic approaches to the problem of epistemic belief-justification: internalism and externalism. It aims to show that internalism as wel as externalism, when confronted with the problem of philosophical skepticism, face various kinds of problems, which lead to implausibility of their respective accounts of justification. The author focuses especially on the externalist approach which was invented as a direct response to the threat of skepticism. The central part of the article contains a brief analysis of main attributes of externalism, and subsequently its criticism which aims to show that the criteria of justification proposed by externalists do not accomplish the basic function of distinguishing between justified and unjustified beliefs. The author argues that the discussed deficiencies of externalism result from its elementary rationale, which implies that they are incurable, and therefore the externalist criteria of justification inevitably fail.
Keywords: epistemology; externalism; internalism; justification; skepticism